Amplification of a chromosomal region in Bacillus subtilis. - Albertini, A M (1985)
We report on the amplification in Bacillus subtilis of a defined DNA sequence after exposure of the bacteria to increasing levels of antibiotic. The experimental system consisted of transformation of competent cells with a plasmid (pRHA39) unable to replicate in the host and carrying the alpha-amylase gene derived from B. subtilis. Selection of transformants resistant to 5 micrograms of chloramphenicol per ml resulted in the isolation of strains with the plasmid integrated into the chromosome at the site of homology, by a Campbell type mechanism. Starting from such a nontandem duplication, amplification was achieved by growing the bacteria in increasing concentrations of chloramphenicol. By dilution, Southern blotting, and hybridization to a radioactive probe, we estimated a copy number of about 10 for the amplified sequence of samples grown in the presence of 50 micrograms of chloramphenicol per ml. No free plasmid could be detected in the amplified strains. The extent of the amplified region was the same for all transformants, and the endpoints appeared to be the same in all isolates. As a consequence of the amplification, there was a noticeable increase in amylase production, and the amount of enzyme produced correlated with gene dosage. The amplification did not occur in a recE genetic background.